BREAK THE CHAIN OF TERRORISM THROUGH DERADICALIZATION OF (FORMER) TERRORISTS’ CHILDREN: NARRATION FROM AL-HIDAYAH PESANTREN, MEDAN - Gayatri, Erin; Kosasih, Kustini (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
Many countries strongly rely on deradicalization path to solve terrorism catastrophe. However, they mostly still focus on the terrorists themselves and lack of attention to the people around them particularly their children. While in some local to the international cases of terrorism, children have involved actively in those acts. This article delivers a significant instance on how to avert the new generation of terrorism particularly from the kinship path. This article focuses on an Islamic boarding school or pesantren (Al-Hidayah) run by a former terrorist (Al-Ghazali) with the main purpose is deradicalization program towards the terrorists’ children. This article is based on the field research, the collecting of the data using depth interview as the primer data and exposure some references as the secondary data. This article found that deradicalization towards terrorist’s children is better under the education platform or pesantren, because it provides two things; firstly, children can gain their right to reach the education after they were marginalized even excluded from their former school. Secondly, it becomes a new home for the children where support the way to apply deradicalization program through the formal model (within the class) and informal model (out the class). There are four significant prograsm that Al-Hidayah pesantren applied namely a green school, life skill, tahfiz class, and trauma healing. Generally, it is success as a curative and preventive action. Although the pesantren receives some financial supports from the government and some other parties, it still struggles to raise more funds to provide free education for its student.